PENERAPAN PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENTS (TGT) DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA SMP PADA TOPIK BILANGAN BULAT - Imam Winaryo; Euis Tuti Himayah (Universitas Sultan Ageng Tirtayasa, 2018)
This research is motivated by the low of learning mastery in the subjects of mathematics, especially on the topic of integers. This is evidenced by looking at data in the academic year 2014/2015 and reinforced the results of interviews with students. In addition, the low achievement of students due to some of the following factors are the low of involvement of students in the process of teaching and learning activities (KBM), and the process of teaching and learning activities is not implemented as it should. With this research is expected to improve the quality of mathematics learning in general and in particular will improve student learning outcomes, especially in SMP Negeri 17 Kota Serang. The problems raised in this research is whether by applying cooperative learning model type TGT can improve student learning outcomes of class VII SMP Negeri 17 Kota Serang on the topic of integer academic year 2015/2016. This study is expected to improve student learning outcomes and achieve learning mastery. Research procedure through three cycles. Each cycle consists of planning, action, observation, and reflection. From the analysis results obtained mastery learning students on the topic of integers increased. This is seen in the improvement of learning completeness of each cycle, ie in the first cycle of 76.6% to 85.3% in cycle II, and on the third cycle increased again by 87.7%. Based on the analysis and discussion got conclusion that the implementation of cooperative learning model type TGT can improve student learning outcomes on the subject of integers. Keywords: Cooperative Learning, Temas Games Tournaments, Learning Outcomes